2021
DOI: 10.1155/2021/6670212
|View full text |Cite
|
Sign up to set email alerts
|

Sauchinone Blocks Ethanol Withdrawal-Induced Anxiety but Spares Locomotor Sensitization: Involvement of Nitric Oxide in the Bed Nucleus of the Stria Terminalis

Abstract: Both the positive (manifested by locomotor sensitization) and negative (withdrawal symptoms) reinforcing effects of ethanol (EtOH) involve central nitric oxide (NO) signaling. Sauchinone (a bioactive lignan in Saururus chinensis) has been shown to improve methamphetamine-induced behavioral and neurochemical changes via the NO signaling pathway. Thus, this study evaluated the effects of sauchinone on locomotor sensitization and anxiety during EtOH withdrawal (EtOHW). Male adult Sprague-Dawley rats were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The EPM was 80 cm elevated from the floor. The methods according the references of Jiao ( Jiao et al, 2021 ) with some modifications. Rats were placed on the central platform facing an open arm individually, and the activity of the rat in the maze for 5 min was recorded by an automated video tracking system.…”
Section: Methodsmentioning
confidence: 99%
“…The EPM was 80 cm elevated from the floor. The methods according the references of Jiao ( Jiao et al, 2021 ) with some modifications. Rats were placed on the central platform facing an open arm individually, and the activity of the rat in the maze for 5 min was recorded by an automated video tracking system.…”
Section: Methodsmentioning
confidence: 99%
“…A wide range of neurotransmitters and neuropeptides, including glutamate, gamma-aminobutyric acid (GABA), nitric oxide (NO), galanin, and neuropeptide Y, are present in the NTS-A2 and regulate NE neuronal activities [ 17 ]. It is well documented that NO synthase (NOS) inhibiters have anxiolytic effects [ 18 20 ]; moreover, the NO system plays an important role in EtOHW anxiety and NE release induced by drug abuse. Bonassoli et al [ 21 ] reported that EtOHW activated NO-producing neurons in the brainstem, while local infusion of NOS inhibitors into the brainstem regions such as the periaqueductal gray matter area and the dorsal raphe nucleus mitigates EtOHW anxiety [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%